Analysis of mercury and other heavy metals accumulated in lichen Usnea antarctica from James Ross Island, Antarctica - Zvěřina, Ondřej; Láska, Kamil; Cervenka, Rostislav; Kuta, Jan; Coufalík, Pavel; Komárek, Josef (Environmental monitoring and assessment, 2014)
The study was designed to investigate the content and distribution of selected heavy metals (As, Cd, Co, Cr, Cu, Hg, Mn, Ni, Fe, Pb and Zn) in samples of fruticose macrolichen Usnea antarctica from James Ross Island. A special emphasis was devoted to mercury and its species (elemental mercury and methylmercury). It was found that mercury contents were relatively high (up to 2.73 mg kg(-1) dry weight) compared to other parts of the Antarctic Peninsula region, while the concentrations of most other elements were within reported ranges. Mercury contents in lichens originating from the interior were higher than those from the coast, which is probably the result of local microclimate conditions. Similar trends were observed for Hg(0) and MeHg(+), whose contents were up to 0.14 and 0.098 mg kg(-1) dry weight, respectively. While mercury did not show a significant correlation with any other element, the mutual correlation of some litophile elements probably refers to the influence on thalli of resuspended weathered material. The influence of habitat and environmental conditions could play an essential role in the bioaccumulation of contaminants rather than just the simple presence of sources. Thus, the study of the thalli of this species can bring a new perspective on the interpretation of contaminant accumulation in lichens of the polar region.
Keywords: lišejníky; ostrovy; ekosystém; rtuť; Ecosystem; Mercury; Islands; Usnea; těžké kovy; Antarktida; Metals, Heavy; Antarctic Regions; Lichens; Environmental Monitoring; monitorování životního prostředí